2018
DOI: 10.1111/1758-2229.12694
|View full text |Cite
|
Sign up to set email alerts
|

Marine biofilms: diversity of communities and of chemical cues

Abstract: Summary Surfaces immersed in seawater are rapidly colonized by various microorganisms, resulting in the formation of heterogenic marine biofilms. These communities are known to influence the settlement of algae spores and invertebrate larvae, triggering a succession of fouling events, with significant environmental and economic impacts. This review covers recent research regarding the differences in composition of biofilms isolated from different artificial surface types and the influence of environmental fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 220 publications
(337 reference statements)
1
61
0
Order By: Relevance
“…On the surface of glass slides deployed for up to 3 weeks at different water depths (5,10,20,40,80 and 160 m) in Loch Fyne, Clyde Sea, W Scotland, Head et al [58] using epifluorescence and bright field microscopy found a seasonal variability in the composition of microbial biofilm. In April, the biofilm community varied significantly with depth, although this effect was ascribable to changes in the diatom community.…”
Section: Glassmentioning
confidence: 99%
See 4 more Smart Citations
“…On the surface of glass slides deployed for up to 3 weeks at different water depths (5,10,20,40,80 and 160 m) in Loch Fyne, Clyde Sea, W Scotland, Head et al [58] using epifluorescence and bright field microscopy found a seasonal variability in the composition of microbial biofilm. In April, the biofilm community varied significantly with depth, although this effect was ascribable to changes in the diatom community.…”
Section: Glassmentioning
confidence: 99%
“…These microbial structures include several levels of structural and functional complexity, which are continuously adapted to the environmental conditions of marine ecosystems. The physical structure, community composition and function of microbial biofilms are controlled by a wide range of physical, chemical and biological variables and processes [2,10], including environmental interactions, interactions with topography, nutrient and organic matter cycling, and photosynthesis. In turn, biofilms are able to influence ecosystem functioning ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations